2022
DOI: 10.1002/alz.12785
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the relationship of subjective cognitive decline and depressive symptoms in the development of cognitive decline and dementia

Abstract: Introduction Subjective cognitive decline (SCD) and depressive symptoms (DS) frequently co‐occur prior to dementia. However, the temporal sequence of their emergence and their combined prognostic value for cognitive decline and dementia is unclear. Methods Temporal relationships of SCD, DS and memory decline were examined by latent difference score modeling in a high‐aged, population‐based cohort (N = 3217) and validated using Cox‐regression of dementia‐conversion. In 334 cognitively unimpaired SCD‐patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Kleineidam et al. ( 35 ) reported that subjective cognitive decline precedes depressive symptoms in the development of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Kleineidam et al. ( 35 ) reported that subjective cognitive decline precedes depressive symptoms in the development of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data now raise the possibility that the combination of an assessment of SCD with cognitive testing could offer a suitable approach to identify high-risk groups for clinical progression. Research on the combination of SCD and MNPD with the assessment of depressive symptoms 34 or broader neuropsychiatric concepts, such as mild behavioral impairment, 35 may further promote the identification of clinical phenotypes of AD that precede the onset of MCI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, using data from the Alzheimer’s Disease Neuroimaging Initiative (ADNI), several NPS profiles exhibited different ratios of conversion to dementia but no association with the CSF AD-core biomarker status. However, a recent cross-sectional study [ 20 ] using a large sample of community-dwelling individuals reported that CSF Aβ42, T-tau/Aβ42 and p-tau/Aβ42 levels were associated with depression, and a prospective study including subjective cognitive decline (SCD) participants of the German Dementia Competence Network (DCN) study, CSF Aβ42 was found associated with an increment in depression severity over time [ 21 ].…”
Section: Discussionmentioning
confidence: 99%